A novel modification to TW-GIA for controlling heat input of base metal. Issue 2 (25th January 2023) - Xu, Guomin; Xu, Xinkun; Lv, Xinze; Liu, Liming
ABSTRACT: Bypass coupling triple-wire gas indirect arc welding (TW-GIA) has been proposed to control the heat input of base metal and consequently improve the weld forming as per the requirement. The influence of the bypass current on arc behavior, welding stability, and weld forming have been investigated. Results showed that the wetting angle and reinforcement reduced gradually, and the weld bead penetration increased with the bypass current increase. The reason was that the workpiece heating mode was changed due to the bypass circuit coupling. It was observed that the heat source was composed of two indirect arcs and two direct arcs, and they were in a coupling state. When the bypass current was 280 A, the electrical parameters of arc fluctuations were at a maximum, and the coupled arc state was not conducive to obtain a stable welding process. Compared to the lack of sidewall fusion and incomplete joint penetration defects of the weld with TW-GIA, the good butt joint of 12 mm thickness steel plates was successfully obtained with bypass coupling TW-GIA under the same energy consumption.